Literasi Keuangan Memoderasi Pengaruh Overconfidence dan Risk Aversion Terhadap Keputusan Investasi Emas - Setyowati, Widhy; Setiyono, Taufiq Andre (Universitas Pamulang, 2025)
Gold is one of the precious metals highly sought after by investors. Its price tends to increase and is highly liquid. Investing in gold carries lower risks compared to investing in other types of assets. This research aims to prove the influence of overconfidence and risk aversion on gold investment decisions with financial literacy moderation. The object if this research was female employees in the formal sector in Semarang City. The sample was taken using accidental sampling technique with a total sample of 100. This research is used Smarts analysis technique. The research results provide that overconfidence has a significant positive effect on gold investment decisions, as well as risk avoidance has a significant positive effect on investment decisions. However, the test results prove that financial literacy doesn't moderate the influence of risk aversion on investment decisions or the influence of excessive confidence on investment decisions.